The Synergy of Kyai in Developing the Religious Character of Students at the Islamic Boarding School in Correctional Institutions - Zaidatun Nafisah; Aminatuz Zahro; Moses Adeleke Adeoye (Faculty of Education and Teacher Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2024)
Prison is a place to punish through criticism and criticism, but over time the prison has changed into a correctional institution (LAPAS). This research intends to explain Islamic boarding school-based prisoner learning with the influence of the synergy of a leader nicknamed Kyai. The qualitative approach used in this research is a case study. Research data sources are based on primary and secondary data with data collection techniques using interviews, observation, and documentation. The conclusion results show that (1) Religious learning in prisons can develop and grow to achieve better learning so that they can take part in Al-Banjari competitions at the provincial level (2) Implementation of Islamic boarding school-based programs in Lumajang class II B prisons is a program that has only been running for 2 years finally in collaboration with the District Ministry of Religion. Lumajang (3) The leadership concept is not a Kyai like Islamic boarding schools in general, but someone who is ready to be a motivation or trigger for inspiration for prisoners (santri).